A study on the effectiveness of electronic and paper dictionaries: comparing the hybrid use of both and the pure use of either. (2017) - Zou, Di; Xie, Haoran; Wang, Fu Lee; Wong, Tak-Lam; Wu, Qingyuan
Playing an important role in assisting vocabulary acquisition, dictionary use has been studied from various perspectives, among which, investigation of the facilitative effects of dictionary consultation in promoting word learning is a particular focus. However, no research has ever been conducted to compare the effectiveness of various approaches to dictionary consultation (e.g., the pure use of either paper or electronic dictionary, or the hybrid use of both). The present research, therefore, responds to this call and conducts two experiments among 185 language learners to examine the facilitative effects of diverse methods of dictionary use. We also interview the participants to inspect their perceptions of dictionary use. The empirical results demonstrate the superiority of the paper dictionary over the electronic dictionary, the usefulness of repetition, and the greater effectiveness of the hybrid use of both paper and electronic dictionary than the pure use of either. The results also shed light on the factors that are of concern to language learners while using dictionaries. We further conclude this study by highlighting the importance of processing for constructing memory, repetition for consolidating memory, and diversity for reinforcing memory in promoting word learning.